Floristic composition and diversity at Keruing (Dipterocarpus spp.) habitat in Tangkahan, Gunung Leuser National Park, Indonesia - Arida Susilowati; HENTI HENDALASTUTI RACHMAT; DENI ELFIATI; ASEP HIDAYAT; ADHI NURUL HADI; ANITA ZAITUNAH; DARIN NAINGGOLAN; IDA MALLIA GINTING (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Susilowati A, Rachmat HH, Elfiati D, Hidayat A, Hadi AN, Zaitunah A, Nainggolan D, Ginting IM. 2021. Floristic composition and diversity at Keruing (Dipterocarpus spp.) habitat in Tangkahan, Gunung Leuser National Park, Indonesia. Biodiversitas 22: 4448-4456. Dipterocarpus spp., or locally known as Keruing, is a wood-producing tree and has high economic value. Keruing also produces derivative products in oil and oleoresin, which are widely used as raw materials for medicines and perfumes. Keruing natural population has been severely declining caused by habitat alteration and also over exploitation. Therefore, information on the composition and diversity of the floristic community at their habitat is important as an initial step in designing conservation actions. This study aims to determine the floristic composition and diversity at the keruing habitat in the Tangkahan area, Gunung Leuser National Park (Gunung Leuser NP). A line transect has been used to establish a purposive sampling in particular forest areas where the population of the keruing is known to grow naturally. Four line transects, each with five nested plots, totaling 110 plots, were established to gather data at four growth stages. The results found 47 species at the seedling stage, 43 species at the sapling stage, 48 species at the pole stage and 65 species at the tree stage. There were three species of keruing in the research location, namely Dipterocarpus haseltii, Dipterocarpus costulatus and Dipterocarpus elongatus Korth with low IVI values ??at each stage. D. haseltii was only found at the seedling, pole and tree stage with IVI values ??of 0.32, 0.30, and 6.90, respectively. D. costulatus was only found at the tree level with an IVI value of 3.43, while D. elongatus found at the sapling and tree stage with an IVI of 0.30 and 3.42, respectively. The diversity index in the research location was in the medium category at the seedling, sapling, and pole levels with a value of 2.96, 2.86, and 2.92, respectively and was classified as high at the tree level with a value of 3.18. The evenness index (E') in all growth stages is high or evenly distributed with the value of E' > 0.75. The species diversity in research location classified into medium-high category although in each stage showing dynamic on species domination. Disturbed habitat due to illegal logging and land conversion caused a problem on keruing regeneration. Conservation efforts, including active monitoring keruing occurrence, ex-situ conservation, and artificial regeneration, are needed to avoid keruing from extinction.